An Introduction to Chinese Philosophy: Reading Feng Youlan’s A Short History of Chinese Philosophy - GU, Yanshen (Journal of Research for Christianity in China (JRCC), 2024)
Feng Youlan, A Short History of Chinese Philosophy, translated by Tu Youguang. Beijing: Peking University Press, 2013. Includes black-and-white illustrations. 228,000 characters. Price: 49 yuan.